Citra Merek Sebagai Variabel Mediasi Pada Pengaruh Celebrity Endorser Dan Electronic Word Of Mouth Terhadap Keputusan Pembelian Produk Serum Hanasui - Izzulhaq, Amelia Rizky; Arochman, Maqbula (PRAGMATIS, 2025)
The purpose of this study is to determine the influence of celebrity endorsers and electronic word of mouth on the purchase decision of Hanasui serum products, with brand image as a mediator, specifically among Hanasui consumers in Surabaya. This study adopts a quantitative methodology, with the target population consisting of Hanasui consumers in Surabaya. Sampling was conducted using non-probability sampling techniques, specifically purposive sampling, with a total of 105 respondents. Data was collected using a questionnaire, and data analysis was performed using path analysis. The results of the study indicate that celebrity endorsers have a positive influence on brand image but do not significantly influence the brand image of Hanasui serum products in Surabaya. Electronic word of mouth has a positive and significant influence on the brand image of Hanasui serum products in Surabaya. Celebrity endorsers have a positive influence on brand image but do not significantly influence the purchase decision of Hanasui serum products in Surabaya. Electronic word of mouth has a positive and significant influence on the purchase decision of Hanasui serum products in Surabaya. Brand image cannot be used as a mediating variable to explain the influence of celebrity endorsers on the purchase decision of Hanasui serum products in Surabaya. Brand image cannot be used as a mediating variable to explain the influence of electronic word of mouth on the purchase decision of Hanasui serum products in Surabaya.